Silent Infarcts, White Matter Integrity, and Oxygen Metabolic Stress in Young Adults With and Without Sickle Cell Trait. Issue 9 (12th May 2022) - Wang, Yan; Guilliams, Kristin P.; Fields, Melanie E.; Fellah, Slim; Binkley, Michael M.; Reis, Martin; Vo, Katie D.; Chen, Yasheng; Ying, Chunwei; Blinder, Morey; King, Allison A.; Hulbert, Monica L.; et al.
Abstract : Background: Individuals with sickle cell anemia have heightened risk of stroke and cognitive dysfunction. Given its high prevalence globally, whether sickle cell trait (SCT) is a risk factor for neurological injury has been of interest; however, data have been limited. We hypothesized that young, healthy adults with SCT would show normal cerebrovascular structure and hemodynamic function. Methods: As a case-control study, young adults with (N=25, cases) and without SCT (N=24, controls) underwent brain magnetic resonance imaging to quantify brain volume, microstructural integrity (fractional anisotropy), silent cerebral infarcts (SCI), intracranial stenosis, and aneurysms. Pseudocontinuous arterial spin labeling and asymmetric spin echo sequences measured cerebral blood flow and oxygen extraction fraction, respectively, from which cerebral metabolic oxygen demand was calculated. Imaging metrics were compared between SCT cases and controls. SCI volume was correlated with baseline characteristics. Results: Compared with controls, adults with SCT demonstrated similar normalized brain volumes (SCT 0.80 versus control 0.81, P =0.41), white matter fractional anisotropy (SCT 0.41 versus control 0.43, P =0.37), cerebral blood flow (SCT 62.04 versus control, 61.16 mL/min/100 g, P =0.67), oxygen extraction fraction (SCT 0.27 versus control 0.27, P =0.31), and cerebral metabolic oxygen demand (SCT 2.71 versus control 2.70 mL/min/100 g, P =0.96). One per cohort had an intracranial aneurysm. None had intracranial stenosis. The SCT cases and controls showed similar prevalence and volume of SCIs; however, in the subset of participants with SCIs, the SCT cases had greater SCI volume versus controls (0.29 versus 0.07 mL, P =0.008). Of baseline characteristics, creatinine was mildly elevated in the SCT cohort (0.9 versus 0.8 mg/dL, P =0.053) and correlated with SCI volume (ρ=0.49, P =0.032). In the SCT cohort, SCI distribution was similar to that of young adults with sickle cell anemia. Conclusions: Adults with SCT showed normal cerebrovascular structure and hemodynamic function. These findings suggest that healthy individuals with SCT are unlikely to be at increased risk for early or accelerated ischemic brain injury.